Peningkatan Hasil Belajar dan Aktivitas Matematika Siswa Melalui Strategi Pembelajaran Inkuiri pada Kelas XII-MIA-3 MAN 1 Kota Bima Tahun Pelajaran 2021/2022 - Siti Hadiah (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
The purpose of this study: (1) To determine the increase in students' mathematics learning outcomes by using inquiry learning strategies. (2) To find out the increase in the activity of students' mathematics learning processes by using inquiry learning strategies. This research is a Classroom Action Research (PTK) which was carried out at MAN 1 Kota Bima. The research subjects were 32 students of class XII IPA-2 for the academic year 2021/2022 consisting of 13 boys and 19 girls. This study consisted of 2 cycles, namely cycle I consisting of 3 meetings and cycle II consisting of 3 meetings. Tests for students' mathematical communication abilities are carried out at the beginning and end of each cycle. The results of this study can be seen from: (1) The results of the repeat test of students' mathematical abilities in cycle I found an average value of 72.75, 21 people completed, 11 people incomplete, 62.5% classical completeness. (2) The results of the second cycle students' math ability test showed an average score of 82.65, 37 people completed, 3 people did not complete, classical completeness was 92.5%, and students' mathematics learning outcomes increased by 9.5 points. (3) Learning by using inquiry learning strategies makes student activities categorized as good in learning.